Incidence and causes of in-hospital mortality in cardiac device-related infections. (25th November 2020) - Doring, M; Ebert, M; Lucas, J; Hindricks, G; Richter, S
Abstract: Introduction: Cardiac device-related infections (CDRI) are associated with increased in-hospital mortality despite effective treatment by transvenous lead extraction (TLE) and antibiotic therapy. Data on mortality and causes of death are scarce and predictors of mortality are not well defined. Purpose: To analyse the incidence and causes of mortality in CDRI and identify predictors of mortality in a large single centre experience. Methods: All patients undergoing TLE for CDRI in our department between May 2012 and January 2020 were included in a prospective registry. Patient characteristics, procedural and follow-up data were collected and analysed. A Kaplan-Meier analysis was used to analyse the influence of different infection types on mortality. Univariate and multivariate cox regression analysis was applied to identify risk factors for mortality. Results: Among 561 consecutive patients (72±12 years; 77% male) treated for CDRI (51.2% systemic and 48.8% localized infection), 61 patients (10.9%) died during the index hospitalization. The most frequent cause of death was severe systemic infection or sepsis in 38 patients (6.8%), followed by end-stage heart failure (9; 1.6%), respiratory insufficiency (3; 0.5%), ventricular arrhythmias (3; 0.5%), asystole (2; 0.4%), pulmonary embolism (2; 0.4%), acute enteric ischemia (2; 0.4%), mechanical ileus (1; 0.2%), and unwitnessed sudden death (1; 0.2%). Patients who died had significantly more often systemic infections (p<0.001), positive blood cultures (p<0.001), severe renal dysfunction (GFR <30ml/min; p<0.001), heart failure with reduced ejection fraction (HFrEF; p=0.001), and diabetes (p=0.004). Kaplan-Meier survival analysis showed a significantly higher mortality in patients with systemic CDRI as compared to localized infection (log-rank p<0.001). Several factors were predictors of mortality in univariate analysis: systemic infection (HR 4.64, 95% CI 2.18–9.84; p<0.001), GFR <30 ml/min (HR 4.27, 95% CI 2.57–7.09; p<0.001), vegetation in TOE (HR 3.68, 95% CI 1.78–7.43; p<0.001), positive blood cultures (HR 2.52, 95% CI 1.46–4.37; p=0.001), diabetes (HR 1.89, 95% CI 1.12–3.18; p=0.018), HFrEF (HR 1.83, 95% CI 1.09–3.05; p=0.021), tricuspid regurgitation (HR 1.79, 95% CI 1.21–2.65, p=0.004), and days from hospital admission to explant (HR 1.04, 95% CI 1.02–1.06; p<0.001). Multivariate analysis revealed severe renal dysfunction (HR 2.71, 95% CI 1.47–5.00; p=0.001) and days from hospital admission to TLE (HR 1.029, 95% CI 1.004–1.055, p=0.021) as independent predictors of in-hospital mortality. Conclusion: In-hospital mortality in CDRI is particularly high in patients with severe systemic infection and sepsis despite state-of the-art treatment. Delayed TLE is associated with an increased in-hospital mortality. Therefore, TLE should be performed early in the course of CDRI, particularly in patients with severe systemic infection. Funding Acknowledgement: Type of funding source: None